Study of opaque phases in carbonatites of the Grønnedal-Íka alkaline complex, Southwest Greenland - Ranta, Eemu (Stockholms universitet, Institutionen för geologiska vetenskaper, 2015)
Opaque phases from carbonatites of the Grønnedal-Íka alkaline complex (1299±17 Ma) of Southwest Greenland were analyzed in terms of their mineralogy and microstructure. The analysis demonstrates that a later intrusion by a 55 m wide dolerite dyke of unknown age has prompted the mineralization of magnetite by activating hydrothermal fluid convection. The fluid has interacted with the carbonatite, replacing siderite and ankerite by magnetite, which at places constitutes over half of the rock volume. Magnetite is shown to have become partly replaced by hematite at a later stage. A paragenetic sequence is suggested for the opaque phases that com- prise major magnetite and hematite, accessory pyrite and trace amounts of sphalerite, chalcopyrite and galena. Low-temperature geologic sequestration of carbon by ikaite formation